The Development of a Realistic Mathematics-Based E-Module Using Project Assignments to Improve Students' Concept Understanding - Rodi'ah, Siti; Hasanah, Isatul; Choir, Jihan Alhanin; Afifah, Laila (Al-Aulad: Journal of Islamic Primary Education, 2024)
The objectives of elementary school mathematics learning are to encourage students to solve problems in everyday life that require a good understanding of concepts. The fact is that student's understanding of concepts at Aisyiyah Innovative Elementary School and Modern Sakti MI is still need improvement. The reason is that teaching materials and teaching strategies don't support students' conceptual understanding. The objectives of this study are, (1) to describe the design of a realistic mathematics-based e-module (RME) with project assignments, and (2) to describe the effect of a realistic mathematics-based e-module (RME). Assist project assignments in improving students' conceptual understanding. This study uses 7 steps Borg &Gall development model adopted by Sugiyono, which are potentials and problems, data collection, product design, design validation, design revision; product trials, and usage trials. The results of the percentage assessment of the questionnaire included material experts 90%, linguists 86.67%, media experts 84.5%, teachers 80%, and students 83.6%. The results of the t-test of the post-test value of the experimental class and the control class showed a sig-2-tailed value of 0. 000 < 0.05. So it can be concluded that the design of a realistic mathematics-based e-module (RME) with project assignments fulfills process, structure, component, and user requirements and effectively improve students' conceptual understanding.Keywords: Concept Understanding, E-Module Development, Realistic Mathematics (RME), Project Assignments,